ANALYSIS OF DIURNAL VARIATION OF PM2.5 CONCENTRATION AND TRAJECTORY ON EXTREME DAYS IN JULY 2023 IN SOUTH TANGERANG - Nabila, Tsuraya
South Tangerang is a rapidly developing city, with most of its areas dominated by residential zones and industrial activities. The city is in a lowland region with elevations ranging from 0 to 62,5 meters above sea level. The highest population density is recorded in Pamulang District, with over 360.000 inhabitants. According to the Nafas report (2023), South Tangerang ranked first as the city with the highest PM2.5 concentration in Indonesia in July 2023, with an average PM2.5 level reaching 60 ?gm-3, classified under the "unhealthy" air quality index according to WHO and US EPA standards. Therefore, it is essential to identify the diurnal variation of PM2.5 concentration and analyze pollutant trajectories on extreme days to understand the spread of pollutants in South Tangerang. This study utilized PM2.5 concentration data from five sensor points across South Tangerang, measured both spatially and temporally during extreme days in July 2023. Additionally, wind speed and direction data from the Budiarto Meteorological Station (ISD_Lite) and meteorological data from ERA5 reanalysis were used. These data were processed to determine how meteorological conditions and wind patterns contributed to the accumulation of pollutants as well as the potential spread of PM2.5 during these extreme days. The results showed that the highest PM2.5 concentration occurred during the early morning (00.00–06.00 WIB) when wind speeds ranged from 0.5 to 0.7 m/s, with winds predominantly blowing from the southwest (higher elevations) to the northeast (lower elevations), and during the evening (16.00–23.00 WIB) when wind speeds ranged from 2.0 to 0.1 ms-1, with winds blowing from the north (lower elevations) to the south (higher elevations). The highest recorded concentration, 117.79 ?gm-3, was observed in the Serpong area. The relationship between PM2.5 concentration, wind speed, and wind direction indicated a strong negative correlation (-0.68), where a decrease in wind speed led to an accumulation of PM2.5. However, wind speed and direction were not the only factors influencing the increase in PM2.5 concentration. On extreme pollution days, forward trajectory analysis showed that pollutants spread toward the northwest (Serang and Tangerang Regency), while backward trajectory analysis indicated that pollutants originated from industrial areas in the southeast (Bogor Regency and Depok)